Using Context to Learn Matrices Concepts Meaningfully - Yoppy Wahyu Purnomo; Nurlaela Rahmawati; Kadir Kadir (Universitas Ahmad Dahlan, 2021)
Mathematical concepts will be embedded if they can be imagined and appear in everyday life. Therefore, this study aims to develop Local Instructional Theory in context-based matrix learning. Design research is adopted to achieve these objectives. The design research has three stages, namely, preliminary experiment, teaching experiment, and retrospective analysis. The study was conducted at a high school on the outskirts of the capital, involving 39 students of class XI. The data was collected employing tests, observation, interviews, worksheets, and documentation in the form of video recordings, photos, and student journals. The results indicated that students were able to construct their concept of matrices through the context of a favorite or a hobby as a starting point in compiling and defining a matrix, and continued with the matrix multiplication concept (matrix scalar multiplication as repeated addition; terms and products of two matrices).